T&T Clark handbook of Christian ethics - Winright, Tobias L. (London ; New York : : T&T Clark, 2021)
"The T&T Clark Handbook of Christian Ethics provides an ecumenical introduction to Christian ethics, its sources, methods, and applications. With contributions by theological ethicists known for their excellence in scholarship and teaching, the essays in this volume offer fresh purchase on, and an agenda for, the discipline of Christian ethics in the 21st century. The essays are organized in three sections, following an introduction that presents the four-font approach and elucidates why it is critically employed through these subsequent sections. The first section explores the sources of Christian ethics, including each of the four fonts: scripture, tradition, experience, and reason. The second section examines fundamental or basic elements of Christian ethics and covers different methods, approaches, and voices in doing Christian ethics, such as natural law, virtue ethics, conscience, responsibility, narrative, worship, and engagement with other religions. The third section addresses current moral issues in politics, medicine, economics, ecology, criminal justice and other related spheres from the perspective of Christian ethics, including war, genetics, neuroethics, end-of-life decisions, marriage, family, work, sexuality, nonhuman animals, migration, aging, policing, incarceration, capital punishment, and more"--
Includes bibliographical references and index.
Description based on print version record
Keywords: Christian ethics